Motivations of sustainable entrepreneurship and their impact of enterprise performance in Gauteng Province, South Africa. Issue 2 (26th February 2018) - Nhemachena, Charles; Murimbika, McEdward
Abstract: The paper discussed motivations of sustainable entrepreneurship in Gauteng Province, South Africa, and estimated relationships between these motivations and enterprise performance. Despite the growing field of sustainable entrepreneurship, most of the available literature has been mainly theoretical and qualitative or has focused on developed countries. This paper contributes to addressing this gap through empirical analysis based on primary survey data from 91 sustainable entrepreneurs. Reliability of the performance and motivation scales were subjected to the Cronbach's alpha coefficient test, and the results were acceptable. The exploratory factor analysis indicated that the motivations of sustainable entrepreneurship factored into 4 dimensions: extrinsic, intrinsic, income security and financial independence, and necessity motivations. Regression analysis revealed that extrinsic and intrinsic motivations are important determinants of enterprise performance. These motivations can be targeted to promote sustainable entrepreneurship in addition to complementary support such as improving business management skills and competencies of sustainable entrepreneurs.